Temperature and annealing time influences on cross-rolled 7475-T7351 aluminum alloy - Diniz,Saulo Brinco (2022)
ABSTRACT During production and heat treatments of aluminum alloys, numerous second phase particles form, which maximizes their mechanical properties. This work aimed to perform a correlation between Vickers hardness and X-ray diffraction results, when 7475-T7351 aluminum alloy processed by the cross rolling is subjected to annealing heat treatments (AHT) at 500 °C for different soaking times (15, 30 and 60 minutes) and for a soaking time of 15 minutes at different temperatures (200, 300 and 400 °C). The influence of the AHT (500 °C / 15 minutes) on the microstructure, via scanning and transmission electron microscopy, and tensile tests properties was also investigated. The results show evidence that the Vickers hardness decreased for AHT performed at 200 and 300 °C / 15 minutes and increase for greater temperatures and times. This behavior is probably due to modifications in the constituent/dispersoid particles and aluminum matrix observed from the X-ray analysis. Partial recrystallization and a coarsening of the precipitates was observed after the AHT at 500 °C / 60 minutes, whose brought harmful effects on the tensile mechanical properties.